(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of the paper is to analysis the agriculture production trend in Gujarat. It has been identified that there are variations in the production of various crops year on year. Mostly these variations are related to fluctuation in monsoon and agriculture policy of the government. Mostly the credit is given to south west monsoon, soil health analysis, states assistance in seed farm, kruchi- Mahotsav, water resource development, additional water storage and maintaining the water resources etc. This simple analysis is done using secondary data. Data has is taken from RBI. Data reveals that in the last one decade there has been an extraordinary growth in Gujarat agriculture. The growth rates have been better than states like Maharashtra and Rajasthan.